On democracy - Dahl, Robert A., 1915-2014; Shapiro, Ian (New Haven : Yale University Press, 2015)
Overview: Written by the preeminent democratic theorist of our time, this book explains the nature, value, and mechanics of democracy. This new edition includes two additional chapters by Ian Shapiro, Dahl's successor as Sterling Professor of Political Science at Yale and a leading contemporary authority on democracy. One chapter deals with the prospects for democracy in light of developments since the advent of the Arab spring in 2010. The other takes up the effects of inequality and money in politics on the quality of democracy, a subject that was of increasing concern to Dahl in his final years.
Preface to the second edition / Ian Shapiro -- Note on the text / Ian Shapiro -- Do we really need a guide? -- Part 1: Beginning: -- We Really Need A Guide? -- Where and how did democracy develop? a brief history -- What lies ahead? -- Ideal democracy -- Part 2: Ideal Democracy: -- What is democracy? -- Why democracy? -- Why political equality 1? Intrinsic equality -- Why political equality 2? Civil competence -- Part 3: Actual Democracy: -- What political institutions does large-scale democracy require? -- Varieties 1: Democracy on different scales -- Varieties 2: Constitutions -- Varieties 3: Parties and electoral systems -- Part 4: Conditions Favorable And Unfavorable: -- What underlying conditions favor democracy? -- Why market-capitalism favors democracy -- Why market-capitalism harms democracy -- Unfinished journey -- Part 5: After On Democracy / Ian Shapiro: -- Continuing the journey? -- Democracy and inequality -- Appendix A: On electoral systems -- Appendix B: Political accommodation in culturally or ethnically divided countries -- Appendix C: On counting democratic counties -- Appendix D: On counting democratic countries 2 -- Notes -- Further reading -- Acknowledgments -- Index.
Includes bibliographical references (pages 245-249) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Democracy; Democracy; Démocratie.; democracy; 89.35 democracy; POLITICAL SCIENCE -- General; Democracy; Democratie; Democracia; Philosophie politique; Démocratie.